PWE-199 Quality of flexible sigmoidoscopy for colorectal cancer screening: are we there yet?. (28th May 2012) - Butt, S K; Defoe, H; Besherdas, K
Abstract : Introduction: Colorectal cancer (CRC) screening with flexible sigmoidoscopy (FS) has been associated with reduced incidence and mortality from CRC. The NHS in UK is introducing FS screening for all men and women at 55 years of age following a multicentre randomised controlled trial which found that FS was a safe and practical test which, when offered only once conferred a substantial and lasting benefit. Quality in performance of FS will be important for success within the screening programme. One aspect of quality of FS performance is the depth of insertion. The definition of an adequately inserted screening FS is subjective and not currently defined. However, in clinical practice, one should examine as much of the distal colon as possible, recognising that it can be difficult to precisely define the furthest extent. It is expected that the rectum and sigmoid colon should be inspected completely and the descending and more proximal colon can often also be visualised. By taking the analogue of colonoscopy one could expect the "decending colon intubation rate" to be at least 90%. In addition, the preparation should be such that the endoscopist is confident that lesions other than small polyps (5 mm or smaller) are not obscured. If adequate insertion is not achieved or the sigmoid colon is not adequately prepared, the procedure may have to be repeated increasing the burden on an already overstretched endoscopy service. Methods: To assess the completion rate (depth of insertion in FS) defined as examination up to at least the decending colon and reasons for incompletion. A single centre, retrospective study in a district general hospital endoscopy unit in London of consecutive FS over a 2-month period in 2011. The FS reports were scrutinised for depth of insertion and if splenic/decending colon was not reached the reason for this. Results: Within the study period, the splenic flexure was reached in 40% (58 of a 148), and the decending colon in 66% (94 of 148). The reasons stated for not reaching the decending colon/splenic flexure include: inadequate bowel prep (26/148), pathology encountered (16/148), patient discomfort (4/148), planned limited procedure (7/148). In 87/148 no reason for not reaching the splenic flexure/decending was documented. Conclusion: In this study, in the majority of patients undergoing FS the splenic flexure in not reached. Only 66% of patients have the rectum and sigmoid colon assessed during planned FS. The reasons for failure of examination to decending colon is not documented in the majority, and this may be because clear guidelines on "decending colon intubation rates" are not available. In order to implement FS as screening for CRC we recommend development of clear quality standard including one of depth of intubation (or "decending colon intubation rate") as is currently available for colonoscopy. Competing interests: None declared.